A novel integrated socio-ecological-economic index for assessing heat health risk - Xihan Yao; Shan Jin; Zhuohui Zhao; Ranhao Sun; Chunfang Wang; Zhaowu Yu (Ecological Indicators)
Extreme heat events caused by climate change and rapid urbanization are major environmental issues affecting the health of urban populations, especially in metropolitan areas. However, few studies have employed a systematic risk assessment model to delineate heat health risk (HHR) in rapidly urbanizing metropolitan areas at a finer resolution, and rare studies have used epidemiological approaches for validation, as mortality is typically considered the most crucial indicator for assessing health impact. Here, a novel integrated socio-ecological-economic index (SEEI) was used to analyze the spatial distribution and evolution of HHR with a neighborhood resolution in Shanghai from 2000 to 2020, and four heat-related mortality indicators were applied to validate. The results showed that (1) the spatial distribution of the SEEI in Shanghai exhibited significant differences between urban and suburban areas, with the main urban areas having an average SEEI 2–3 times higher than suburban areas. (2) Overall, the SEEI peaked in 2010 and declined in 2020, with very high-risk neighborhoods decreasing from seven in 2000 to none in 2020. However, there was a slight trend towards a wider range of moderate-risk neighborhoods. (3) The heat-related mortality indicators exhibited significant correlations with SEEI, demonstrating the reliability of the SEEI as also confirmed by sensitivity analysis. The SEEI used in this study can provide a basis for decision-making for Shanghai as well as similar metropolitan areas to prevent extreme heat events.